DEEP MARKETING STRATEGY ANALYSIS INCREASING PRODUCT SALES AT PRINTMATE INDONESIA LTD. IN MEDAN - Kesuma, Yuliana; Sahputra, Ngatno; Firah, Al (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
Problem identification in this study is the existence of competitors with similar products. The marketing strategy carried out is still not right in increasing sales, sales instability and sales targets have not been achieved. This type of research uses qualitative methods. Data collection techniques use observation, interviews and documentation. Data analysis techniques use SWOT analysis by analyzing internal and external factors regarding the strengths, weaknesses, opportunities and threats owned by the company. The results of the study were based on SWOT analysis at Printmate Indonesia Ltd. in Medan showed that the company obtained an IFAS score of 72.78 USD which means that the company has a fairly strong internal position, while the EFAS score value of 75.45 USD which shows that the company can respond to opportunities. This shows that the company is in quadrant I, so the right strategy is to use a strategy to support aggressive growth policies (growth oriented strategy).